2012
DOI: 10.2147/jpr.s27751
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplastic alteration of TTX-resistant sodium channel with visceral pain and morphine-induced hyperalgesia

Abstract: The discovery of the tetrodotoxin-resistant (TTX-R) Na+ channel in nociceptive neurons has provided a special target for analgesic intervention. In a previous study we found that both morphine tolerance and persistent visceral inflammation resulted in visceral hyperalgesia. It has also been suggested that hyperexcitability of sensory neurons due to altered TTX-R Na+ channel properties and expression contributes to hyperalgesia; however, we do not know if some TTX-R Na+ channel property changes can be triggered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…NaV1.9, a tetrodotoxin (TTX) resistant sodium channel is involved in cold sensation, 58 and TTX resistant channels, including NaV1.9, are upregulated by morphine or morphine’s metabolite M3G. 11, 27 The response of the TRPM8 channel, however, would not depend on the presence of NaV1.9, since the NaV1.9 KO mice still respond to TRPM8/TRPA1 blockers. 58 Finally, we can speculate that a downregulation of the TASK-3 leak potassium channel in a subpopulation of TRPM8 neurons 64 might also be involved in the increased cold sensitivity in morphine treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…NaV1.9, a tetrodotoxin (TTX) resistant sodium channel is involved in cold sensation, 58 and TTX resistant channels, including NaV1.9, are upregulated by morphine or morphine’s metabolite M3G. 11, 27 The response of the TRPM8 channel, however, would not depend on the presence of NaV1.9, since the NaV1.9 KO mice still respond to TRPM8/TRPA1 blockers. 58 Finally, we can speculate that a downregulation of the TASK-3 leak potassium channel in a subpopulation of TRPM8 neurons 64 might also be involved in the increased cold sensitivity in morphine treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Nassirpour's work showed that primary hippocampal neuron culture incubated with 100 lM morphine for 20 h exhibited significant inhibition on excitatory and inhibitory synaptic transmission, which was mediated by the activation of G-protein-activated inwardly rectifying potassium channel (GIRK) (Nassirpour et al, 2010). It's well recognized that adaptive change theories, including synaptic transmission and alterations in neuronal excitability after chronic morphine treatments are another facet of the mechanisms underlying the development of tolerance (Chen et al, 2012a;Mao et al, 2002a;Zhao and Joo, 2006). Most importantly, based on this culture model, significant elevations in Akt phosphorylation and increased IL-1b release resulting from enhanced Caspase-1 maturation and NALP1 inflammasome activation after morphine incubation were observed.…”
Section: Establishment Of Sustained Morphine Incubation Model In Vitromentioning
confidence: 99%
“…Voltage-gated sodium channels are critical to the action potential upstroke and altered sodiumchannel kinetics in acute and chronic morphine-treated DRG and myenteric neurons have been demonstrated previously (Chen et al, 2012;Smith et al, 2012Smith et al, , 2014Mischel et al, 2018). Analysis of single-cell RNA sequencing data from Zeisel at al.…”
Section: Discussionmentioning
confidence: 99%